Smoking Cessation Counseling Program: A Pilot Study on College Smokers - Surachman, F; Anggadiredja, K; Rahmawati, S F; Zazuli, Z (KnE Life Sciences, 2019)
Smoking is one of the major problems of public health in Indonesia, but the effort from the government, especially in the light of health-related aspect, for smoking cessation program is still lacking. Pharmacists have a role in facilitating smoking cessation intervention through counseling and pharmacotherapy. The purpose of this prospective study was to determine whether counseling can reduce the number of the cigarette smoked and nicotine dependence (based on Fagerström Test for Nicotine Dependence (FTND) score), also improve the quality of life (based on Smoking Cessation Quality of Life (SCQOL)) on college smokers. There were 12 pharmacy students trained as counselors using Rx for Change training module. After the training, there were significant increases in counseling skills and confidence aspects (p<0.01), but not in the perceived-role. From 188 respondents who are a current cigarette smoker, 17 agreed to participate and finished all four counseling sessions (30 days point-prevalence). By the end of the program, 3 (17.65%) had abstinence, 11 (64.70%) reduced their smoking consumption per day by ≥ 50%, while three others (17.65%) relapsed. Counseling had a positive impact on reducing nicotine dependence based on FTND score improvement (p<0.01), but not on the quality of life. Counseling as a method to reduce smoking is considered effective and applicable to be adapted by pharmacy students and pharmacists. For long-term cessation and its impact, participants’ progress should be followed-up at longer point-prevalence and verified biochemically to prevent bias. Keywords: counseling, pharmacy students, smoking cessation, nicotine dependence, quality of life